МАТЕМАТИЧНІ МОДЕЛІ МОНІТОРИНГУ ВІДКЛАДЕНЬ ОЖЕЛЕДІ ТА ЗМІНИ СТРІЛИ ПРОВИСАННЯ ПРОВОДІВ ПОВІТРЯНИХ ЛІНІЙ ЕЛЕКТРОПЕРЕДАВАННЯ - Кацадзе, Т.Л.; Буслова, Н.В.; Новіков, К.М.; Ніколаєва, А.Д. (Інститут електродинаміки Національної академії наук України, 2024)
The paper presents the results of studing the problem of monitoring the condition of an overhead power line wire. The known approaches to the formation of a device for monitoring the sagging boom and ice-coating on the line wires are analysed. It is shown that one of the most promising approaches is based on measuring the angle of inclination of the wire sagging curve near the point of its fixation on the support. It is shown that an unambiguous correlation between the slope angle of the sagging curve and the wire sagging arrow allows for an indirect measurement of the operating temperature of the wire in the absence of ice deposits. It has been shown that equipping the monitoring device with a temperature sensor will allow monitoring the weight of ice-coating and, if necessary, issuing a signal for organising anti-icing measures. Modification of the device with a three-axis gyroscopic sensor allows for additional monitoring of wind pressure on overhead line wires. The paper presents mathematical models for solving these problems of monitoring the condition of the wire.